Peranan Kualitas Pelayanan Terhadap Kepuasan Peserta Pelatihan (Studi Kasus pada Ibu-ibu Rumah Tangga di Bedahan, Sawangan, Depok - Fadli Rasam; Elin Karlina; Ani Interdiana Candra Sari (Universitas Indraprasta PGRI, 2022)
The reason for this study is to make parameters in the success of counseling programs for the community, especially housewives, and assess deficiencies for further improvement, while the purpose of this study is to obtain empirical answers and know the Role of Service Quality towards Training Participant Satisfaction (Case Study on Housewives in Sawangan, Surgery). This research was conducted in Bedahan, Sawangan Depok with 20 respondents. The method used is a survey with a simple linear regression analysis approach. Based on research and SPSS calculations, the results of the study obtained there was a positive and significant influence on the variable quality of services provided by lecturers on the satisfaction received by the training participants. Consumer satisfaction is a response to the behavior shown by consumers by comparing performance or perceived results with expectations. If the perceived results are below expectations, then consumers will be disappointed, dissatisfied, and even dissatisfied, but on the contrary, if they match expectations, consumers will be satisfied and if the performance exceeds expectations, consumers will be very satisfied. Customer satisfaction is influenced by the perception of service quality, product quality, price, and factors that are personal and that are momentary situations.